Black in Time: How #BlackLivesMatter Reorients the Human - Louis M Maraj (Revista Brasileira de História da Mídia, 2022)
This essay discusses how Black Lives Matter activists make meaning in relation to history, temporality, and anti-Blackness in the Western world. It analyzes the modalities through which these activists frame resistance, paying particular attention to the movement’s attempts to, in the words of co-founder Alicia Garza, “(re)build the Black liberation movement” (2014) through Black feminist epistemologies. By looking at how the movement pushes against antiBlackness intersectionally through in-person and digital and protests and in popular culture, we might come to understand why it has garnered global significance in reshaping past conceptions of what it means to be “human.”